2017
DOI: 10.1097/md.0000000000008585
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence of periodontitis in Taiwan from 1997 to 2013

Abstract: Periodontitis is one of the most prevalent oral diseases. In this study, we probed the nationwide registered database to assess the time trends of prevalence of periodontitis in Taiwan.A retrospective study was conducted to analyze the registered database compiled by the National Health Insurance provided by the Department of Health, Taiwan, from 1997 to December 2013.We found that the prevalence of periodontitis significantly increased from 11.5% in 1997 to 19.59% in 2013 (P for trend < .0001). The mean age ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
3
26
2
Order By: Relevance
“…The US study showed a prevalence of PPD ≥5 mm was 19.6% from 2009 to 2012, and Korea's health protection data showed that the prevalence of periodontitis was 31% from 2002 to 2013 . Moreover, we previously reported that the prevalence rate of periodontal disease in Taiwan increased from 11.5% in 1997 to 19.59% in 2013, and this prevalence rate is similar to this study. Third, liver abscesses are endemic to Southeast Asian countries and Taiwan.…”
Section: Discussionsupporting
confidence: 88%
“…The US study showed a prevalence of PPD ≥5 mm was 19.6% from 2009 to 2012, and Korea's health protection data showed that the prevalence of periodontitis was 31% from 2002 to 2013 . Moreover, we previously reported that the prevalence rate of periodontal disease in Taiwan increased from 11.5% in 1997 to 19.59% in 2013, and this prevalence rate is similar to this study. Third, liver abscesses are endemic to Southeast Asian countries and Taiwan.…”
Section: Discussionsupporting
confidence: 88%
“…The source population consisted of nearly the entire population of Taiwan (23 million inhabitants), which was covered by the National Health Insurance (NHI). [ 32 34 ] The study used the Longitudinal Health Insurance Database (LHID) obtained from the NHI Research Database (NHIRD), consisting of 1 million beneficiaries randomly sampled from the original NHI beneficiaries. [ 35 , 36 ] The National Health Research Institute in Taiwan permitted the access to the data in the NHIRD and the database includes the entire registry and claims data from this this health insurance system.…”
Section: Methodsmentioning
confidence: 99%
“…[ 35 , 36 ] The National Health Research Institute in Taiwan permitted the access to the data in the NHIRD and the database includes the entire registry and claims data from this this health insurance system. [ 32 37 ] The accuracy of diagnosis in the NIRD has been validated for several diseases, including stroke and CKD. [ 37 39 ] To minimize the bias of uncertain diagnosis for GC in the current study, the following strategy was used.…”
Section: Methodsmentioning
confidence: 99%
“…Asian Americans experienced a mean attachment loss of 1.95 mm and 15.4% had clinical attachment loss (CAL) ≥7 mm [ 6 ]. In addition, a study of PD prevalence in Taiwan showed that the prevalence of PD gradually rose from 11.5% in 1997 to 19.59% in 2013 during the 17-year study period [ 7 ].…”
Section: Introductionmentioning
confidence: 99%